Sustained release of N‐acetylcysteine by sandwich structured polycaprolactone/collagen scaffolds for wound healing. Issue 7 (5th March 2019) - Hou, Jinfei; Chen, Lifeng; Liu, Zhirong; Li, Jialun; Yang, Jie; Zhong, Aimei; Zhou, Muran; Sun, Yang; Guo, Liang; Yang, Yanqing; Sun, Jiaming; Wang, Zhenxing
Abstract: PCL (poly‐caprolactone) nanofibers have good biocompatibility and high porosity, which are usually utilized for application in wound dressings. However, wound healing could be hindered by the overproduction of reactive oxygen species (ROS) and different factors. Pure nanofibers cannot satisfy these requirements of wound healing. N ‐acetylcysteine (NAC), as an antioxidant, meets the requirements for wound healing by resisting the overproduction of ROS and by promoting angiogenesis and maturation of the epidermis. In this study, we prepared a sandwich structured PCL‐Col/NAC scaffold using the molding method, which consisted of PCL nanofibers at the core and NAC‐loaded collagen on both sides. The hydroscopicity and tensile modulus of PCL‐Col/NAC scaffolds showed best performance of these properties among groups. Meanwhile, the drug release profiles of PCL‐Col/NAC scaffolds were investigated using the HPLC method and the results suggested a sustained drug release of NAC for PCL‐Col/NAC scaffolds. In addition, PCL‐Col/NAC scaffolds presented better properties than the control groups in cell migration and proliferation. The in vivo wound healing therapy effect was studied using an oval (2 × 1 cm) full‐thickness skin defect wound model for SD rats. After 21 days, gross view and histological analysis showed a favorable beneficial therapeutic effect as well as better epidermal maturation compared with the control groups. CD31 immunohistology results revealed relatively more new vessels in the PCL‐Col/NAC group than the control groups. This study developed novel PCL‐Col/NAC scaffolds with an excellent hydroscopicity, tensile modulus and the ability to promote epidermal maturation and angiogenesis, demonstrating its promising potential in wound healing treatment. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2019.